2023
DOI: 10.3389/fpsyg.2023.1151518
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the neurobiology of Merge at a basic level: insights from a novel artificial grammar paradigm

Abstract: IntroductionHuman language allows us to generate an infinite number of linguistic expressions. It’s proposed that this competence is based on a binary syntactic operation, Merge, combining two elements to form a new constituent. An increasing number of recent studies have shifted from complex syntactic structures to two-word constructions to investigate the neural representation of this operation at the most basic level.MethodsThis fMRI study aimed to develop a highly flexible artificial grammar paradigm for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 168 publications
0
10
0
Order By: Relevance
“…In addition, the activation of LIFG directly correlates with the syntactic complexity as shown by the studies focusing on the processing of noncanonical sentences involving word scrambling, syntactic movement, and multiple syntactic embeddings (e.g., Ben-Shachar et al, 2004;Caplan et al, 2008;Friederici et al, 2006b;Makuuchi et al, 2009Makuuchi et al, , 2013Meyer et al, 2012;Röder et al, 2002;Santi & Grodzinsky, 2010). Evidence of artificial hierarchical grammar processing from Chen et al (2021a) and Liu et al (2023) further indicated that LIFG engages in the build-up process of syntactic hierarchies.…”
Section: Pfc Engagement In Sentence Processingmentioning
confidence: 91%
See 4 more Smart Citations
“…In addition, the activation of LIFG directly correlates with the syntactic complexity as shown by the studies focusing on the processing of noncanonical sentences involving word scrambling, syntactic movement, and multiple syntactic embeddings (e.g., Ben-Shachar et al, 2004;Caplan et al, 2008;Friederici et al, 2006b;Makuuchi et al, 2009Makuuchi et al, , 2013Meyer et al, 2012;Röder et al, 2002;Santi & Grodzinsky, 2010). Evidence of artificial hierarchical grammar processing from Chen et al (2021a) and Liu et al (2023) further indicated that LIFG engages in the build-up process of syntactic hierarchies.…”
Section: Pfc Engagement In Sentence Processingmentioning
confidence: 91%
“…Moreover, word frequencies and the frequencies of collocation between two nouns/verbs or a noun and a verb were carefully controlled so that participants were unable to process the sentences or make judgements with any possible strategies unrelated to language processing. Following Xu et al (2020) and Liu et al (2023), a probing statement of thematic relation (i.e., the relation of "who did what to whom") was attached to each sentence trail for the correctness judgement to detect participants' performance of syntactic processing (Figure 2A). The probing sentences were also controlled regarding the collocation frequencies between words and the frequencies of probing verbs with respect to their location (i.e., in main clauses or relative clauses), with half being correct/incorrect.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations